2022
DOI: 10.1371/journal.pgen.1010139
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of osteopontin in patients with chronic kidney disease: The German Chronic Kidney Disease study

Abstract: Osteopontin (OPN), encoded by SPP1, is a phosphorylated glycoprotein predominantly synthesized in kidney tissue. Increased OPN mRNA and protein expression correlates with proteinuria, reduced creatinine clearance, and kidney fibrosis in animal models of kidney disease. But its genetic underpinnings are incompletely understood. We therefore conducted a genome-wide association study (GWAS) of OPN in a European chronic kidney disease (CKD) population. Using data from participants of the German Chronic Kidney Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 104 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…The chromosome location of the OPN gene varies by species; for example, the gene in human, and mice is located on chromosomes 4, and 5, respectively [16]. A genome-wide association of a European CKD population revealed two replicated loci, one upstream of SPP1, and another mapping onto KLKB1 encoding pre-kallikrein, which is involved in blood pressure control, inflammation, cancer, and cardiovascular disease [12]. An important paralog of KLKB1 is F11, which is associated with OPN expression in several tissues.…”
Section: Molecular Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosome location of the OPN gene varies by species; for example, the gene in human, and mice is located on chromosomes 4, and 5, respectively [16]. A genome-wide association of a European CKD population revealed two replicated loci, one upstream of SPP1, and another mapping onto KLKB1 encoding pre-kallikrein, which is involved in blood pressure control, inflammation, cancer, and cardiovascular disease [12]. An important paralog of KLKB1 is F11, which is associated with OPN expression in several tissues.…”
Section: Molecular Structure and Functionmentioning
confidence: 99%
“…Among all tissues, kidneys have the greatest OPN content [12]. In normal kidneys, OPN is mainly expressed in the loop of Henle and the distal nephron [13], but following kidney damage, its expression is upregulated in all tubular segments and in the glomeruli by as much as 18-fold [13].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies may help discern whether lowering osteopontin levels is ‘causally related’ with the risk of kidney failure. Another study from the GCKD cohort identified two replicated polymorphisms that were associated with serum osteopontin levels: one close to the SPP1 gene, encoding osteopontin, and another one that mapped to the KLKB1 gene encoding prekallikrein, which is processed to kallikrein [ 12 ]. Kallikrein, in turn, has been implicated through the kinin-kallikrein system in blood pressure control, inflammation, blood coagulation, cancer, and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin (SPP1), which is overexpressed in various malignancies promoting proliferation, migration, and invasion, is normally expressed in the bile duct epithelium, and represents a suitable, early diagnostic marker for hepatocarcinoma [ 15 ]. In renal tissues, SPP1 has been correlated with proteinuria, reduced creatinine clearance, and kidney fibrosis in animal models of kidney diseases [ 16 ]. In the liver, vascular endothelial growth factor (VEGF) is the main regulator of angiogenesis, and its expression was correlated with bile duct growth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%